Implications Of Misunderstandings In Radiotelephony Aeronautical Communication Between Pilots And Atc Towards Flight Safety: An Aerolinguistic Study (Journal of Namibian Studies : History Politics Culture, 2023)
It is crucial for all parties involved in aviation, including pilots, ATC, and APP, to communicate clearly and follow established procedures to ensure flight safety. Missunderstanding of in communication and instruction implementation can have fatal consequences, and therefore must be avoided with utmost seriousness.Therefore, in translating and understanding speech acts in aeronautical radiotelephony conversations, researchers must discuss them with pilot informants or aeronautical experts, especially those who understand radiotelephony. Aeronautical terminology is well understood by pilots, ATC personnel, individuals involved in the aviation field, or those who have studied and practiced radiotelephony directly. Another interesting and crucial aspect of aeronautical radiotelephony conversations is the pilot's obligation to perform readbacks for every imperative statement from ATC. Additionally, speech acts in aeronautical radiotelephony conversations always seek feedback in the form of perlocution from the conversation partners. If speech acts in aeronautical radiotelephony conversations do not adhere to the regulations set by ICAO Annex 10, misunderstandings can occur, potentially leading to fatal aircraft accidents.Data from (www.planecrashinfo.com) shows statistics of accidents involving all types of commercial aircraft worldwide from the 1950s to the 2000s. On average, pilot error accounts for 50% of accidents, followed by mechanical failure at 22%, weather at 12%, sabotage at 9%, other human factors at 7%, and other factors at 1%. Similarly, in national aviation, it is suspected that the high frequency of incidents and airplane accidents is related to factors involving human error.